A New Role for an Old Drug: Metformin Targets MicroRNAs in Treating Diabetes and Cancer. Issue 6 (September 2015) - Zhou, Joseph Yi; Xu, Biao; Li, Lixin; Gurwitz, David
ABSTRACT <table-wrap position="anchor" orientation="portrait"> Preclinical Research </table-wrap> MicroRNAs (miRNAs) are a family of short, noncoding, 19–23 base pair RNA molecules. Due to their unique role in gene regulation in various tissues, miRNAs play important roles in regulating insulin secretion, metabolic disease, and cancer biology. Emerging evidence demonstrates that miRNAs could also be novel diagnostic markers for a variety of disease states. Additionally, miRNAs have been found to function either as oncogenes, or tumor suppressor genes in cerian cancers. An increasing number of studies have been conducted investigating new drugs targeting miRNAs as a potential anticancer therapy. Metformin is the most widely prescribed medication for treating Type 2 diabetes (T2D). Recent clinical data suggests that metformin impacts the miRNA profile in T2D subjects. Most excitingly, studies have found that metformin is protective against cancer. The anticancer activity of metformin is mediated through a direct regulation of miRNAs, which further modulates several downstream genes in metabolic or preoncogenic pathways. These miRNAs are, therefore, prospective therapeutic targets for treating diabetes and cancer which is the topic of this review. Further study on the regulation of miRNAs by metformin could result in novel therapeutic strategies for recurrent or drug‐esistant cancer, and as part of combinatorial approaches with conventional anticancer therapies. Drug Dev Res 76 : 263–269, 2015. © 2015 Wiley Periodicals, Inc.